Returns to Education in Europe – Detailed Results from a Harmonized Survey - Torge Middendorf (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
We use the European Community Household Panel, a harmonized data set covering the countries of the European Union, to provide detailed estimates of the returns to education. Our results can be summarized as follows. Firstly, average returns to education have been mostly stable during the second half of the 1990s and are highest in Portugal and Ireland and lowest in the UK and Italy. Secondly, returns to schooling are significantly negatively related to the educational attainment of the population. Thirdly, for most countries we find significant cohort effects and these are in general uniform across countries implying lower returns to education for younger cohorts. Fourthly, in most countries schooling exerts a significantly stronger impact on wages at the top of the wage distribution, aggravating within-group inequality. Finally, we provide evidence that the more pronounced the difference in returns to education along the wage distribution, the higher the average return to education.
Keywords: I21; J24; J31; 330; Returns to schooling; cohort effects; quantile regression; Bildungsertrag; Privater Haushalt; Schätzung; EU-Staaten